Urbanism in the steppe Volga Region in the XIII–XV centuries - Zeleneev Yury A. (Поволжская археология)
In the middle of the XIII century there were no cities on the territory of the Golden Horde steppe Volga region. They began to form gradually from settlements that served the economic needs of the nomadic elite. The settlement and then the city of Ukek (Uvek ancient settlement) belongs to such settlements. Similar reasons are for the formation of the settlement, and then the city of Beldjamen (Vodyansk settlement). The city that existed on the site of the Tsarev settlement arises not only as an economic, but also as an administrative center. The final decline of the steppe cities of the Volga region falls on the period of the Great Troubles (the Golden Horde Dynastic War). After it, at the end of the XIV century, we see a short-term attempt to restore them, which had no results.